Inorganic filler dispersion stabilizer, resin composition containing inorganic filler, molded product and additive

By using polyester with carboxyl groups at both ends in the resin composition to form a three-dimensional network, the viscosity increase and settlement problems caused by the increase of inorganic fillers are solved, and the viscosity adjustment and storage stability are improved.

CN115298262BActive Publication Date: 2024-12-20DIC CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202180022046.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-03-25
Filing Date
2021-03-04
Publication Date
2024-12-20
Estimated Expiration
2041-03-04

AI Technical Summary

Technical Problem

Increasing the fill amount of inorganic filler in the resin composition will lead to a rise in viscosity and a decrease in formability, and existing viscosity reducing agents cannot effectively reduce viscosity and prevent the settlement of inorganic filler, affecting storage stability.

Method used

Polyesters with carboxyl groups at both ends are used as the inorganic filler dispersion stabilizer, and a three-dimensional network is formed through its interaction with the inorganic filler to regulate viscosity and prevent settlement.

Benefits of technology

The viscosity of the composition containing inorganic filler is effectively reduced, storage stability is improved, and the viscosity is appropriately reduced when used to improve formability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

Provided is an inorganic filler dispersion stabilizer capable of reducing the viscosity of a composition containing an inorganic filler and improving the storage stability of the composition containing an inorganic filler. The inorganic filler dispersion stabilizer is a polyester having carboxyl groups at both ends.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an inorganic filler dispersion stabilizer, a resin composition containing an inorganic filler, a molded product and an additive. Background Art

[0002] Building materials, automobile components, sanitary absorbent articles, stone paper, etc. are formed from resin compositions containing inorganic fillers, and various functions such as impact resistance, bending resistance, dimensional stability, and moisture permeability are imparted by the inorganic fillers.

[0003] In order to improve the functionality of the molded product and to reduce the cost due to the increase in volume, it is required to further increase the amount of inorganic filler. However, if the amount of inorganic filler in the resin composition is increased, the fluidity of the resin composition is reduced and the moldability is reduced.

[0004] For example, in the application of urethane waterproof floor materials, calcium carbonate is generally used as an inorganic filler. However, increasing the amount of calcium carbonate filled increases the viscosity, which deteriorates the moldability and handling properties.

[0005] As a method for increasing the content of the inorganic filler in the resin composition, a method of adding a viscosity reducing agent has been adopted, and various viscosity reducing agents have been proposed (Patent Documents 1 and 2).

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2011-079935

[0009] Patent Document 2: Japanese Patent Publication No. 54-34009 Summary of the invention

[0010] Problems to be solved by the invention

[0011] The above-mentioned viscosity reducing agent suppresses the interaction between inorganic fillers by coating the surface of the inorganic filler, thereby reducing the viscosity of the composition. On the other hand, by reducing the viscosity of the composition, the inorganic filler settles over time to form an agglomerate (hard cake) containing the inorganic filler, which has the problem of significantly impairing storage stability.

[0012] In addition, depending on the type of binder resin contained in the composition, the above-mentioned viscosity reducing agent may not exhibit a viscosity reducing effect.

[0013] The problem to be solved by the present invention is to provide an inorganic filler dispersion stabilizer capable of reducing the viscosity of a composition containing an inorganic filler and improving storage stability.

[0014] Means for solving problems

[0015] The present inventors have conducted intensive studies to solve the above problems and have found that a polyester having a specific structure can reduce the viscosity of a resin composition containing an inorganic filler and improve the storage stability, thereby completing the present invention.

[0016] That is, the present invention relates to an inorganic filler dispersion stabilizer which is a polyester having carboxyl groups at both ends.

[0017] Effects of the Invention

[0018] According to the present invention, an inorganic filler dispersion stabilizer capable of reducing the viscosity of a composition containing an inorganic filler and improving the storage stability of the composition containing an inorganic filler can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a graph showing the measurement results of the dispersion stabilizer C produced in Example 3 by MALDI-TOFMS (matrix-assisted laser desorption ionization-time of flight mass spectrometry). DETAILED DESCRIPTION

[0020] Hereinafter, an embodiment of the present invention will be described. The present invention is not limited to the following embodiment, and can be implemented with appropriate modifications within a range that does not impair the effects of the present invention.

[0021] [Inorganic filler dispersion stabilizer]

[0022] The inorganic filler dispersion stabilizer of the present invention is a polyester having carboxyl groups at both ends. Hereinafter, the inorganic filler dispersion stabilizer of the present invention is sometimes referred to as "the dispersion stabilizer of the present invention", and the polyester serving as the inorganic filler dispersion stabilizer of the present invention is sometimes referred to as "the polyester of the present invention".

[0023] In the present invention, the "dispersion stabilizer" refers to a component which is added to a composition containing an inorganic filler to prevent the inorganic filler in the composition from aggregating and settling.

[0024] In the polyester of the present invention, it is considered that one of the carboxyl groups at both terminals is adsorbed to the inorganic filler and the other carboxyl group is adsorbed to the other inorganic filler, thereby forming a three-dimensional network composed of the polyester and the inorganic filler.

[0025] It is believed that when the shear force is very small, such as when the composition is stored, the three-dimensional network maintains its form, increases the viscosity of the system and inhibits the sedimentation of the inorganic filler. On the other hand, when the shear force is large, such as when the composition is used, the three-dimensional network is temporarily destroyed by the shear force and dispersed, which can reduce the viscosity of the system. This effect can be expected to be unaffected by various binder resins used in the composition.

[0026] The polyester of the present invention is preferably a polyester having carboxyl groups at both ends, and having a repeating unit represented by the following general formula (1-1) and a repeating unit represented by the following general formula (1-2), or having a repeating unit represented by the following general formula (1-1), a repeating unit represented by the following general formula (1-2), and a repeating unit represented by the following general formula (1-3).

[0027]

Chemical formula 1

[0028]

[0029] (In the above formulas (1-1), (1-2) and (1-3),

[0030] A is an aliphatic dibasic acid residue having 2 to 12 carbon atoms,

[0031] G is an aliphatic diol residue having 2 to 9 carbon atoms,

[0032] L is a hydroxycarboxylic acid residue having 2 to 18 carbon atoms.

[0033] The polyester of the present invention is more preferably a polyester having a repeating unit represented by the above general formula (1-1) and a repeating unit represented by the above general formula (1-2) and having carboxyl groups at both terminals.

[0034] The polymerization form of the polyester having the repeating unit represented by the above general formula (1-1), the repeating unit represented by the above general formula (1-2) and the repeating unit represented by the above general formula (1-3) is not particularly limited, and it may be a random copolymer of these repeating units or a block copolymer of these repeating units.

[0035] The polyester of the present invention is more preferably a polyester represented by the following general formula (1).

[0036]

Chemical formula 2

[0037]

[0038] (In the above general formula (1),

[0039] A1 is an aliphatic dibasic acid residue having 2 to 12 carbon atoms.

[0040] A2 and A3 are each independently an aliphatic polybasic acid residue having 2 to 12 carbon atoms or an aromatic polybasic acid residue having 6 to 15 carbon atoms.

[0041] G1 and G2 are each independently an aliphatic diol residue having 2 to 9 carbon atoms.

[0042] m represents the number of repetitions, and is an integer in the range of 1-20.

[0043] p is an integer obtained by subtracting 1 from the number of acid functional groups of the aliphatic polybasic acid or aromatic polybasic acid of A2.

[0044] q is an integer obtained by subtracting 1 from the number of acid functional groups of the aliphatic polybasic acid or aromatic polybasic acid of A3.

[0045] In each repeating unit enclosed in brackets, A1 and G1 may be the same or different.)

[0046] In the present invention, "diacid residue" refers to an organic group obtained by removing an acid functional group from a dibasic acid. For example, when the dibasic acid residue is a dicarboxylic acid residue, the dicarboxylic acid residue refers to an organic group remaining after removing a carboxyl group possessed by the dicarboxylic acid. The number of carbon atoms in the dicarboxylic acid residue does not include the carbon atoms in the carboxyl group.

[0047] In the present invention, "polyacid residue" refers to an organic group obtained by removing an acid functional group from a polyacid having two or more acid functional groups. For example, when the polyacid residue is a dicarboxylic acid residue, a tricarboxylic acid residue or a tetracarboxylic acid residue, the dicarboxylic acid residue, the tricarboxylic acid residue or the tetracarboxylic acid residue represents an organic group remaining after removing the carboxyl group they have. The carbon atom numbers of the dicarboxylic acid residue, the tricarboxylic acid residue and the tetracarboxylic acid residue do not include the carbon atoms in the carboxyl group.

[0048] In the present invention, "diol residue" and "alcohol residue" refer to an organic group remaining after removing a hydroxyl group from a diol or an alcohol.

[0049] In the present invention, "hydroxycarboxylic acid residue" means an organic group remaining after removing a hydroxyl group and a carboxyl group from a hydroxycarboxylic acid, respectively. The number of carbon atoms in the hydroxycarboxylic acid residue does not include the carbon atoms in the carboxyl group.

[0050] The aliphatic dibasic acid residue having 2 to 12 carbon atoms of A and A1 may contain an alicyclic structure.

[0051] The aliphatic dibasic acid residue having 2 to 12 carbon atoms of A and A1 is preferably an aliphatic dicarboxylic acid residue having 2 to 12 carbon atoms, and examples of the aliphatic dicarboxylic acid residue having 2 to 12 carbon atoms include a succinic acid residue, an adipic acid residue, a pimelic acid residue, a suberic acid residue, azelaic acid residue, a sebacic acid residue, a cyclohexanedicarboxylic acid residue, a dodecanedicarboxylic acid residue, and a hexahydrophthalic acid residue.

[0052] The aliphatic dibasic acid residue having 2 to 12 carbon atoms of A and A1 is preferably an aliphatic dicarboxylic acid residue having 4 to 10 carbon atoms, more preferably an aliphatic dicarboxylic acid residue having 5 to 10 carbon atoms, and further preferably a sebacic acid residue or a dodecanedicarboxylic acid residue.

[0053] The aliphatic polybasic acid residue having 2 to 12 carbon atoms of A2 and A3 may contain an alicyclic structure.

[0054] The aliphatic polybasic acid residue having 2 to 12 carbon atoms of A2 and A3 is preferably an aliphatic dicarboxylic acid residue having 2 to 12 carbon atoms, and examples of the aliphatic dicarboxylic acid residue having 2 to 12 carbon atoms include a succinic acid residue, an adipic acid residue, a pimelic acid residue, a suberic acid residue, azelaic acid residue, a sebacic acid residue, a cyclohexanedicarboxylic acid residue, a dodecanedicarboxylic acid residue, a hexahydrophthalic acid residue, and a maleic acid residue.

[0055] The aromatic polyacid residue having 6 to 15 carbon atoms of A2 and A3 is preferably an aromatic dicarboxylic acid residue having 6 to 15 carbon atoms, an aromatic tricarboxylic acid residue having 6 to 15 carbon atoms, or an aromatic tetracarboxylic acid residue having 6 to 15 carbon atoms, and examples thereof include phthalic acid residues, trimellitic acid residues, pyromellitic acid residues, and the like.

[0056] Examples of the aliphatic diol residue having 2 to 9 carbon atoms of G, G1 and G2 include an ethylene glycol residue, a 1,2-propylene glycol residue, a 1,3-propylene glycol residue, a 1,2-butylene glycol residue, a 1,3-butylene glycol residue, a 2-methyl-1,3-propylene glycol residue, a 1,4-butylene glycol residue, a 1,5-pentanediol residue, a 2,2-dimethyl-1,3-propylene glycol residue (neopentyl glycol residue), a 2,2-diethyl -1,3-propanediol (3,3-dihydroxymethylpentane) residue, 2-n-butyl-2-ethyl-1,3-propanediol (3,3-dihydroxymethylheptane) residue, 3-methyl-1,5-pentanediol residue, 1,6-hexanediol residue, 2,2,4-trimethyl-1,3-pentanediol residue, 2-ethyl-1,3-hexanediol residue, 2-methyl-1,8-octanediol residue, 1,9-nonanediol residue, etc.

[0057] The aliphatic diol residue having 2 to 9 carbon atoms of G, G1 and G2 may contain an alicyclic structure and / or an ether bond.

[0058] Examples of the aliphatic diol residue having 2 to 9 carbon atoms and containing an alicyclic structure include a 1,3-cyclopentanediol residue, a 1,2-cyclohexanediol residue, a 1,3-cyclohexanediol residue, a 1,4-cyclohexanediol residue, a 1,2-cyclohexanedimethanol residue, and a 1,4-cyclohexanedimethanol residue.

[0059] Examples of the aliphatic diol residue having 2 to 9 carbon atoms and containing an ether bond include a diethylene glycol residue, a triethylene glycol residue, a tetraethylene glycol residue, a dipropylene glycol residue, and a tripropylene glycol residue.

[0060] The aliphatic diol residue having 2 to 9 carbon atoms of G, G1 and G2 is preferably an aliphatic diol residue having 3 to 8 carbon atoms, more preferably a 2-methyl-1,3-propanediol residue, 3-methyl-1,5-pentanediol, 1,3-propanediol, a propylene glycol residue or a diethylene glycol residue.

[0061] As the hydroxycarboxylic acid residue having 2 to 18 carbon atoms as L, there can be mentioned residues of hydroxycarboxylic acids in which one hydroxy group is substituted on the aliphatic chain of an aliphatic carboxylic acid having 3 to 19 carbon atoms, such as propionic acid, butyric acid, valeric acid, caproic acid, heptanoic acid, decanoic acid, undecanoic acid, lauric acid, tridecanoic acid, myristic acid, pentadecanoic acid, palmitic acid, heptadecanoic acid and stearic acid. Specific examples include lactic acid residues, 9-hydroxystearic acid residues, 12-hydroxystearic acid residues and 6-hydroxyhexanoic acid residues.

[0062] The hydroxycarboxylic acid residue having 2 to 18 carbon atoms of L is preferably an aliphatic hydroxycarboxylic acid residue having 4 to 18 carbon atoms, and more preferably a 12-hydroxystearic acid residue.

[0063] p is an integer obtained by subtracting 1 from the number of acid functional groups of the aliphatic polyacid or aromatic polyacid of A2. Similarly, q is an integer obtained by subtracting 1 from the number of acid functional groups of the aliphatic polyacid or aromatic polyacid of A3. Therefore, when A2 and A3 are each independently an aliphatic dicarboxylic acid residue having 2 to 12 carbon atoms or an aromatic dicarboxylic acid residue having 6 to 15 carbon atoms, the number of acid functional groups (carboxyl groups) possessed by A2 and A3 is 2, p and q are 1, respectively, and the above general formula (1) is as follows.

[0064]

Chemical formula 3

[0065]

[0066] The polyester of the present invention can be used, for example, as a mixture of two or more polyesters having at least one different value of each residue and m in the general formula (1). In this case, the average value of m is preferably in the range of 2 to 15.

[0067] In addition, the average value of m can be confirmed from the number average molecular weight of the polyester.

[0068] The number average molecular weight (Mn) of the polyester of the present invention is, for example, in the range of 100 to 6,000, preferably in the range of 300 to 5,000, more preferably in the range of 500 to 5,000, and further preferably in the range of 800 to 4,500.

[0069] The number average molecular weight (Mn) is a value obtained by measuring with gel permeation chromatography (GPC) and converting it into polystyrene, and is measured by the method described in Examples.

[0070] The acid value of the polyester of the present invention is preferably in the range of 20 to 400 mgKOH / g, more preferably in the range of 30 to 150 mgKOH / g, and even more preferably in the range of 40 to 150 mgKOH / g.

[0071] The acid value of the above polyester is confirmed by the method described in Examples.

[0072] The properties of the polyester of the present invention vary depending on the number average molecular weight, composition, etc., and it is usually in the form of liquid, solid, paste, etc. at room temperature.

[0073] The polyester of the present invention is obtained using a reaction raw material containing an aliphatic dibasic acid, an aliphatic polybasic acid and / or an aromatic polybasic acid, an aliphatic diol, and an arbitrary hydroxycarboxylic acid. Here, the reaction raw material refers to the raw material constituting the polyester of the present invention, and means that a solvent or a catalyst that does not constitute the polyester is not included. In addition, "arbitrary hydroxycarboxylic acid" means that a hydroxycarboxylic acid may be used or not.

[0074] The method for producing the polyester of the present invention is not particularly limited, and the polyester can be produced by a known method or by the production method described below.

[0075] The reaction raw materials of the polyester of the present invention may contain an aliphatic dibasic acid, an aliphatic polybasic acid and / or an aromatic polybasic acid, an aliphatic diol, and any hydroxycarboxylic acid, and may contain other raw materials.

[0076] The reaction raw materials of the polyester of the present invention preferably contain 90% by mass or more of aliphatic dibasic acids, aliphatic polybasic acids and / or aromatic polybasic acids, aliphatic diols, and any hydroxycarboxylic acids relative to the total amount of the reaction raw materials, and more preferably contain only aliphatic dibasic acids, aliphatic polybasic acids and / or aromatic polybasic acids, aliphatic diols, and any hydroxycarboxylic acids.

[0077] The aliphatic dibasic acid used in the production of the polyester of the present invention is an aliphatic dibasic acid corresponding to the aliphatic dibasic acid residue having 2 to 12 carbon atoms of A and A1, and the aliphatic dibasic acid used may be used alone or in combination of two or more.

[0078] The aliphatic polybasic acid used in the production of the polyester of the present invention is an aliphatic polybasic acid corresponding to the aliphatic polybasic acid residues having 2 to 12 carbon atoms of A2 and A3, and the aliphatic polybasic acid used may be used alone or in combination of two or more.

[0079] The aromatic polybasic acid used in the production of the polyester of the present invention is an aromatic polybasic acid corresponding to the aromatic polybasic acid residues having 6 to 15 carbon atoms of A2 and A3. The aromatic polybasic acid used may be used alone or in combination of two or more.

[0080] The aliphatic diol used in the production of the polyester of the present invention is an aliphatic diol corresponding to the aliphatic diol residue having 2 to 9 carbon atoms of G, G1 and G2, and the aliphatic diol used may be used alone or in combination of two or more.

[0081] The hydroxycarboxylic acid used in the production of the polyester of the present invention is a hydroxycarboxylic acid corresponding to a hydroxycarboxylic acid residue having 2 to 18 carbon atoms in L, and the hydroxycarboxylic acid used may be used alone or in combination of two or more.

[0082] The reaction raw materials used also include derivatives such as the above-mentioned esterification products, the above-mentioned acid chlorides, and the above-mentioned acid anhydrides. For example, hydroxycarboxylic acids also include compounds having a lactone structure such as ε-caprolactone.

[0083] The polyester of the present invention can be produced by reacting an aliphatic dibasic acid, an aliphatic polybasic acid and / or an aromatic polybasic acid, an aliphatic diol, and an arbitrary hydroxycarboxylic acid constituting each residue of the polyester of the present invention under the condition that the equivalent of the carboxyl group contained in the reaction raw materials is greater than the equivalent of the hydroxyl group.

[0084] The polyester of the present invention can also be produced by reacting an aliphatic dibasic acid, an aliphatic diol, and any hydroxycarboxylic acid constituting the residues of the polyester of the present invention under conditions where the equivalent of hydroxyl groups contained in the reaction raw materials is greater than the equivalent of carboxyl groups to obtain a polyester having a hydroxyl group at the end of the main chain, and then further reacting the obtained polyester with an aliphatic polybasic acid and / or an aromatic polybasic acid.

[0085] In the production of the polyester of the present invention, the reaction of the above-mentioned reaction raw materials can be carried out by esterification reaction in the presence of a catalyst as needed, for example, at a temperature range of 180 to 250° C. for 10 to 25 hours.

[0086] It should be noted that the conditions such as temperature and time of the esterification reaction are not particularly limited and can be appropriately set.

[0087] Examples of the esterification catalyst include titanium-based catalysts such as tetraisopropyl titanate and tetrabutyl titanate; zinc-based catalysts such as zinc acetate; tin-based catalysts such as dibutyltin oxide; and organic sulfonic acid-based catalysts such as p-toluenesulfonic acid.

[0088] The amount of the esterification catalyst used may be appropriately set, and is usually within a range of 0.001 to 0.1 parts by mass based on 100 parts by mass of the total amount of the reaction raw materials.

[0089] [Resin composition containing inorganic filler]

[0090] The dispersion stabilizer of the present invention can function as a dispersion stabilizer of an inorganic filler in a resin composition containing an inorganic filler and a resin (resin composition containing an inorganic filler), can reduce the viscosity of the composition, and prevent the inorganic filler from agglomerating and settling when the composition is stored for a long time. Among them, since the formation of an agglomerate (hard cake) containing an inorganic filler can be prevented, the dispersion stabilizer of the present invention can particularly function as a storage stabilizer of a resin composition containing an inorganic filler.

[0091] Hereinafter, each component contained in the inorganic filler-containing resin composition of the present invention will be described.

[0092] (Inorganic filler)

[0093] The inorganic filler contained in the inorganic filler-containing resin composition of the present invention is not particularly limited, and examples thereof include calcium carbonate, talc, silica, alumina, clay, antimony oxide, aluminum hydroxide, magnesium hydroxide, hydrotalcite, calcium silicate, magnesium oxide, potassium titanate, barium titanate, titanium oxide, calcium oxide, magnesium oxide, manganese dioxide, boron nitride, aluminum nitride, and the like.

[0094] The above-mentioned inorganic fillers may be used alone or in combination of two or more.

[0095] The inorganic filler is preferably one or more selected from calcium carbonate, silica, alumina, aluminum hydroxide, barium titanate, talc, boron nitride and aluminum nitride, and more preferably one or more selected from calcium carbonate, alumina, aluminum hydroxide and talc.

[0096] The particle size, fiber length, fiber diameter and other shapes of the inorganic filler are not particularly limited and can be appropriately adjusted according to the target application. In addition, the surface treatment state of the inorganic filler is also not particularly limited and can be surface-modified with saturated fatty acids, etc. according to the target application.

[0097] The content of the dispersion stabilizer of the present invention is not particularly limited. For example, the content of the dispersion stabilizer of the present invention is in the range of 0.1 to 30 parts by mass relative to 100 parts by mass of the inorganic filler. Preferably, the content of the dispersion stabilizer of the present invention is in the range of 0.1 to 10 parts by mass relative to 100 parts by mass of the inorganic filler. More preferably, the content of the dispersion stabilizer of the present invention is in the range of 0.1 to 5.0 parts by mass relative to 100 parts by mass of the inorganic filler.

[0098] (Viscosity reducing agent)

[0099] The inorganic filler-containing resin composition of the present invention preferably contains a viscosity reducing agent.

[0100] By making the resin composition containing inorganic filler include a viscosity reducing agent, the filling amount of the inorganic filler can be increased, and the handling property can be improved. The viscosity reducing agent may induce the formation of agglomerates (hard cakes) containing inorganic fillers due to the viscosity reduction of the composition, but the formation of hard cakes can be prevented by the dispersion stabilizer of the present invention. Therefore, in the resin composition containing inorganic filler of the present invention, it is preferred to use the dispersion stabilizer and viscosity reducing agent of the present invention in combination.

[0101] The viscosity reducing agent is not particularly limited, and examples thereof include anionic wetting and dispersing agents, cationic wetting and dispersing agents, and polymeric wetting and dispersing agents.

[0102] Specific examples of the above-mentioned viscosity reducing agent include alkyl ethers, mineral spirits, alkylbenzenes, paraffins, higher fatty acid esters, sorbitan fatty acid esters, glycerol fatty acid esters, polycarboxylates (e.g., polycarboxylic acid alkylammonium salts), polyester acid salts (e.g., polyester acid unsaturated polyaminoamide salts), higher fatty acid amides, polyethylene oxide derivatives, sulfates, hydrogenated stearic acid derivatives, polyalkylene polyimine alkylene oxides, polyallylamine derivatives, polyether ester acid amines, polyether phosphate amines, polycarboxylic acid polyesters, polyesters having a carboxyl group only at one end, etc. Among them, polycarboxylic acid alkylammonium salts, higher fatty acid amides, polyester acid unsaturated polyaminoamide salts, and polyesters having a carboxyl group only at one end are preferred.

[0103] The above-mentioned viscosity reducing agents may be used alone or in combination of two or more.

[0104] As the above-mentioned viscosity reducing agent, a commercially available product can be used. Examples of the commercially available product include ANTI-TERRA series such as ANTI-TERRA-U / U100, ANTI-TERRA-204, and ANTI-TERRA-250; DISPERBYK series such as DISPERBYK-106, DISPERBYK-108, and DISPERBYK-140; BYK series such as BYK-9076 and BYK-9077 (all manufactured by BYK-Chemie); Flowlen series such as Flowlen DOPA-15B, Flowlen DOPA-17HF, and Flowlen DOPA-22; Flownon series such as FlownonRCM-100 (all manufactured by Kyoeisha Chemical); Solsperse 3000, Solsperse 20060, Solsperse 40000, Solsperse 42000, and Solsperse Solsperse series such as 85000 (all manufactured by Lubrizol Corporation); DISPARLON series such as DISPARLON DA-234, DISPARLON DA-325, DISPARLON DA-375 (all manufactured by Kusumoto Chemicals Co., Ltd.); ESLEAM series such as ESLEAM 221P, ESLEAM C2093, ESLEAM AD-374M, ESLEAM AD-508E; Filanol series such as PA-085C, Filanol PA-107P; MALIALIM series such as MALIALIM SC-1015F, MALIALIM SC-0708A, MALIALIM AFB-1521, MALIALIM AAB-0851, MALIALIM AWS-0851 (all manufactured by NOF Corporation); DEMOL DEMOL series such as POIZ 520, POIZ 521, POIZ 530; HOMOGENOL series such as HOMOGENOL L-18 (all manufactured by Kao Corporation); AJISPER series such as AJISPER PB821, AJISPER PB822, AJISPER PB824, AJISPER PB881, AJISPER PN411, AJISPER PA111 (all manufactured by Ajinomoto Fine Techno Co., Ltd.), etc.

[0105] When a polyester having a carboxyl group only at one terminal is used as the above-mentioned viscosity reducing agent, the polyester viscosity reducing agent is preferably a polyester represented by the following general formula (I) or the following general formula (II).

[0106]

Chemical formula 4

[0107]

[0108] (In the above general formulas (I) and (II),

[0109] A 11 It is an aliphatic dicarboxylic acid residue having 2 to 12 carbon atoms.

[0110] G 11 and G 12 Each is independently an aliphatic diol residue having 2 to 9 carbon atoms.

[0111] X is a dicarboxylic acid residue having 1 to 8 carbon atoms.

[0112] Y is a hydrogen atom or a monocarboxylic acid residue having 1 to 9 carbon atoms.

[0113] Z is a monohydric alcohol residue having 2 to 10 carbon atoms.

[0114] t represents the number of repetitions, and is an integer in the range of 0 to 30.

[0115] u represents the number of repetitions, and is an integer in the range of 0 to 30.

[0116] In each bracketed repeating unit, A 11 and G 11 They can be the same or different.)

[0117] The polyester represented by the above general formula (I) or (II) is preferably prepared from the same raw materials as the polyester of the present invention because the repeating unit of the polyester is common.

[0118] In the above general formulae (I) and (II), A 11 an aliphatic dicarboxylic acid residue having 2 to 12 carbon atoms, and G 11 and G 12 The aliphatic diol residue having 2 to 9 carbon atoms is the same as that of the polyester of the present invention.

[0119] The dicarboxylic acid residue having 1 to 8 carbon atoms as X may be any of an aliphatic dicarboxylic acid residue, an alicyclic dicarboxylic acid residue, and an aromatic dicarboxylic acid residue.

[0120] Examples of the aliphatic dicarboxylic acid residue include malonic acid residue, succinic acid residue, glutaric acid residue, adipic acid residue, pimelic acid residue, suberic acid residue, azelaic acid residue, sebacic acid residue, maleic acid residue, fumaric acid residue, 1,2-dicarboxycyclohexane residue, 1,2-dicarboxycyclohexene residue, and the like.

[0121] Examples of the aromatic dicarboxylic acid residue include a phthalic acid residue, an isophthalic acid residue, and a terephthalic acid residue.

[0122] The dicarboxylic acid residue having 1 to 8 carbon atoms represented by X is preferably a succinic acid residue, an adipic acid residue, a maleic acid residue or a phthalic acid residue.

[0123] The monocarboxylic acid residue having 1 to 9 carbon atoms of Y may be any of an aliphatic monocarboxylic acid residue, an alicyclic monocarboxylic acid residue, and an aromatic monocarboxylic acid residue, for example, a propionic acid residue, a butyric acid residue, a hexanoic acid residue, an octanoic acid residue, an octanoic acid residue, a benzoic acid residue, a dimethylbenzoic acid residue, a trimethylbenzoic acid residue, a tetramethylbenzoic acid residue, an ethylbenzoic acid residue, a propylbenzoic acid residue, a butylbenzoic acid residue, a quicalic acid residue, a p-tert-butylbenzoic acid residue, an o-methylbenzoic acid residue, an m-methylbenzoic acid residue, a p-methylbenzoic acid residue, an ethoxybenzoic acid residue, a propoxybenzoic acid residue, anisic acid residue, a naphthoic acid residue, and the like.

[0124] Y is preferably a hydrogen atom or a benzoic acid residue.

[0125] The monoalcohol residue having 2 to 10 carbon atoms of Z may be any of an aliphatic monoalcohol residue and an alicyclic monoalcohol residue.

[0126] Examples of the monohydric alcohol residue having 2 to 10 carbon atoms of Z include ethanol residue, propanol residue, butanol residue, pentanol residue, hexanol residue, cyclohexanol residue, heptanol residue, octanol residue, nonanol residue and decanol residue, among which octanol residue, nonanol residue and decanol residue are preferred.

[0127] In the polyester represented by the general formula (I), Y is preferably a hydrogen atom, an acetyl group or a benzoic acid residue, and G 11 and G 12 Each is independently a propylene glycol residue, a neopentyl glycol residue or a 1,3-propanediol residue, A 11 is an adipic acid residue, and X is an adipic acid residue or a maleic acid residue.

[0128] The polyester represented by the general formula (II) is preferably a octanol residue, a nonanol residue or a decanol residue, and G 11 is a propylene glycol residue, a neopentyl glycol residue or a 1,3-propanediol residue, A 11 is an adipic acid residue, and X is an adipic acid residue or a maleic acid residue.

[0129] The polyester represented by the general formula (I) can be used, for example, as a mixture of two or more polyesters in which at least one of the residues in the general formula (I) and the value of t is different from each other. In this case, the average value of t is preferably in the range of 2 to 15. Similarly, the polyester represented by the general formula (II) can be used, for example, as a mixture of two or more polyesters in which at least one of the residues in the general formula (II) and the value of u is different from each other. In this case, the average value of u is preferably in the range of 2 to 15.

[0130] Furthermore, the polyester represented by the above general formula (I) and the polyester represented by the above general formula (II) may be used in the form of a mixture.

[0131] The average values ​​of t and u can be confirmed from the number average molecular weight of the polyester.

[0132] The acid value of the polyester represented by the general formula (I) or (II) is preferably in the range of 3-50, more preferably in the range of 3-35.

[0133] The acid value of the above polyester is confirmed by the method described in Examples.

[0134] The number average molecular weight (Mn) of the polyester represented by the general formula (I) or (II) is preferably in the range of 300 to 3,000, more preferably in the range of 400 to 2,500, and even more preferably in the range of 400 to 1,500.

[0135] The number average molecular weight (Mn) is a value obtained by measuring with gel permeation chromatography (GPC) and converting it into polystyrene, and is measured by the method described in Examples.

[0136] The properties of the polyester represented by the general formula (I) or (II) vary depending on the number average molecular weight, composition, etc., and it is usually in the form of liquid, solid, paste, etc. at room temperature.

[0137] The polyester represented by the general formula (I) or (II) can be produced in the same manner as the polyester of the present invention. Specifically, there can be mentioned a method in which the above-mentioned diol, dicarboxylic acid, monocarboxylic acid or monohydric alcohol are added together to carry out an esterification reaction; a method in which a compound having hydroxyl groups at both ends is obtained using diol and dicarboxylic acid, and then a monocarboxylic acid is further reacted with a dicarboxylic acid; a method in which a compound having carboxyl groups at both ends is obtained using diol and dicarboxylic acid, and then a monohydric alcohol is further reacted, etc.

[0138] Among the above, the reaction product of an aliphatic dicarboxylic acid having 2 to 12 carbon atoms and an aliphatic diol having 2 to 9 carbon atoms and a monocarboxylic acid having 1 to 9 carbon atoms or a monool having 2 to 10 carbon atoms can be prepared into a mixture of the polyester represented by the above general formula (1) and the polyester represented by the above general formula (I) or (II) as the inorganic filler dispersion stabilizer of the present invention, which is excellent in both viscosity reducing effect and storage stabilization effect and is therefore preferred.

[0139] The content of the viscosity reducing agent is not particularly limited, and is, for example, in the range of 0.1 to 30 parts by mass, preferably 0.1 to 10 parts by mass, based on 100 parts by mass of the inorganic filler.

[0140] (Plasticizer)

[0141] The inorganic filler-containing resin composition of the present invention preferably contains a plasticizer.

[0142] Examples of the plasticizer include benzoates such as diethylene glycol dibenzoate; phthalates such as dibutyl phthalate (DBP), di-2-ethylhexyl phthalate (DOP), diisononyl phthalate (DINP), diisodecyl phthalate (DIDP), diundecyl phthalate (DUP), and ditridecyl phthalate (DTDP); terephthalates such as bis(2-ethylhexyl) terephthalate (DOTP); isophthalates such as bis(2-ethylhexyl) isophthalate (DOIP); pyromellitic acid esters such as tetra-2-ethylhexyl pyromellitic acid (TOPM); di-2-ethylhexyl adipate (DOA), diisononyl adipate (DINA); , diisodecyl adipate (DIDA), di-2-ethylhexyl sebacate (DOS), diisononyl sebacate (DINS) and other aliphatic dibasic acid esters; tri-2-ethylhexyl phosphate (TOP), tritrisyl phosphate (TCP) and other phosphate esters; alkyl esters of polyols such as pentaerythritol; polyesters with a molecular weight of 800 to 4000 synthesized by polyesterification of dibasic acids such as adipic acid and diols; epoxidized esters such as epoxidized soybean oil and epoxidized linseed oil; alicyclic dibasic acids such as diisononyl hexahydrophthalate; fatty acid diol esters such as 1,4-butylene glycol didecanoate; acetyl tributyl citrate (ATBC); chlorinated paraffin obtained by chlorinating paraffin and normal paraffin; chlorinated fatty acid esters such as chlorinated stearic acid esters; higher fatty acid esters such as butyl oleate, etc.

[0143] The plasticizer to be used may be determined according to the intended use, and the above-mentioned plasticizers may be used alone or in combination of two or more.

[0144] The content of the plasticizer is not particularly limited, and is, for example, in the range of 10 to 300 parts by mass of the plasticizer per 100 parts by mass of the inorganic filler, and preferably in the range of 30 to 200 parts by mass of the plasticizer per 100 parts by mass of the inorganic filler.

[0145] The additives contained in the inorganic filler-containing resin composition of the present invention are not limited to the inorganic filler dispersion stabilizer of the present invention, the above-mentioned viscosity reducing agent, and the above-mentioned plasticizer, and other additives besides these may be contained.

[0146] Examples of the other additives include flame retardants, stabilizers, stabilization aids, colorants, processing aids, fillers, antioxidants (antiaging agents), ultraviolet absorbers, light stabilizers, lubricants, antistatic agents, and crosslinking aids.

[0147] (resin)

[0148] The resin contained in the inorganic filler-containing resin composition of the present invention is not particularly limited, and examples thereof include polyolefins, polyesters, polythioethers, polyvinyl chloride, modified polythioethers, silicone resins, modified silicone resins, acrylic urethane resins, epoxy resins, polyurethanes, acrylic resins, polyesters, and unsaturated polyesters.

[0149] The resin to be used may be determined according to the intended use, and the above resins may be used alone or in combination of two or more.

[0150] The inorganic filler-containing resin composition of the present invention contains a resin, but the dispersion stabilizer of the present invention can also be suitably used in a composition containing a viscous compound such as asphalt instead of the resin.

[0151] The inorganic filler-containing resin composition of the present invention can be suitably used as a paste-like resin composition which requires fluidity when used.

[0152] The dispersion stabilizer of the present invention can reduce the viscosity of the composition, inhibit the formation of hard cakes and improve the storage stability of the composition. Therefore, it is preferably used in coatings, adhesives, structural materials, etc. that are mostly used outdoors. It is suitable for two-component urethane floor material coatings that need to be mixed before coating, structural materials (building materials) in which the filler content is expected to be increased, and polysulfide sealing materials with particularly high filler content.

[0153] Hereinafter, composition examples for different applications when the inorganic filler-containing resin composition of the present invention is used as a paste-like resin composition will be described.

[0154] (Structural Materials)

[0155] Examples of the resin contained in the inorganic filler-containing resin composition used in the above-mentioned structural material include polyolefins, polyurethanes, and unsaturated polyesters.

[0156] The resin used in structural materials (building materials) varies depending on the application. For example, in waterproof materials, polyurethane is mainly used as the resin component, while in artificial marble, unsaturated polyester is mainly used.

[0157] When the structural material is a waterproof material, the resin composition containing inorganic fillers used in the waterproof material (hereinafter sometimes referred to as "resin composition for waterproof material") is preferably a polyurethane composition containing a main agent component and a curing agent component, wherein the main agent component contains an isocyanate group-containing compound, and the curing agent component contains one or more selected from aromatic polyamines, polyols, water and moisture.

[0158] The isocyanate group-containing compound contained in the main agent component is preferably an isocyanate group-terminated polyurethane prepolymer obtained by reacting a polyisocyanate having a diphenylmethane diisocyanate structure with a polyol.

[0159] Examples of the polyisocyanate include 4,4'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, and 2,2'-diphenylmethane diisocyanate, of which an isocyanate mixture containing 4,4'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, and / or 2,2'-diphenylmethane diisocyanate is preferred.

[0160] As the polyol, polyoxypropylene polyol is preferred, and polyoxypropylene diol alone or a mixture of polyoxypropylene diol and polyoxypropylene triol is more preferred.

[0161] The ratio of polyisocyanate to polyol in the isocyanate-terminated urethane prepolymer is preferably in the range of 1.8 to 2.5 in terms of the molar ratio of isocyanate group to hydroxyl group (NCO / OH). The isocyanate group content (NCO group content) in the isocyanate-terminated urethane prepolymer is preferably in the range of 2 to 5% by mass.

[0162] Examples of the aromatic polyamine contained in the curing agent component include 4,4'-methylenebis(2-chloroaniline), dimethylthiotoluenediamine, diethyltoluenediamine, etc. Among them, 4,4'-methylenebis(2-chloroaniline) is known as "MOCA" and is widely used.

[0163] As the polyol contained in the curing agent component, polyether polyol is preferred, and polyoxypropylene polyol is particularly preferred. The number of functional groups of the polyol is preferably in the range of 2 to 4, and more preferably in the range of 2 to 3.

[0164] When the polyurethane is a two-component curing type, regarding the mixing ratio of the main agent and the curing agent, the molar ratio of the isocyanate group contained in the main agent to the active hydrogen-containing group contained in the curing agent (NCO / (NH2+OH)) is, for example, in the range of 1.0 to 2.0, preferably in the range of 1.0 to 1.8, and more preferably in the range of 1.0 to 1.3.

[0165] The curing agent component may contain an inorganic filler. Examples of the inorganic filler include calcium carbonate, talc, clay, silica, and carbon.

[0166] The content of the inorganic filler in the polyurethane composition can be set to, for example, 10 to 60 parts by mass, preferably 20 to 50 parts by mass, relative to 100 parts by mass of the resin component. By setting the content of the inorganic filler to this range, the curability of the composition and the performance of the obtained waterproof material can be well balanced.

[0167] In the case of two-component curable polyurethane, usually, the viscosity of the main agent and the curing agent are both high (main agent: for example, in the range of 7 to 10 Pa·S, curing agent: for example, in the range of 10 to 30 Pa·S). In winter when the temperature drops, the viscosity further increases. Therefore, the dispersion stabilizer of the present invention that can improve the dispersibility of the inorganic filler and increase the content is useful.

[0168] The dispersion stabilizer of the present invention may be contained in the resin composition for waterproof materials. For example, in the case of the above-mentioned two-component curable polyurethane, the dispersion stabilizer of the present invention may be contained in at least one of the main component and the curing agent component.

[0169] The curing agent component may contain a known curing catalyst in order to promote the urethanization reaction. Examples of the curing catalyst include organic acid lead, organic acid tin, and tertiary amine compounds.

[0170] The curing agent component may include, in addition to the inorganic filler and the curing catalyst, the above-mentioned viscosity reducing agent, the above-mentioned plasticizer, pigments such as chromium oxide, titanium oxide, and phthalocyanine; antioxidants, ultraviolet absorbing materials, stabilizers such as dehydrating agents, and the like.

[0171] Examples of the waterproof material obtained by molding the waterproof material composition include a roof waterproof material.

[0172] The roof waterproof material is obtained by, for example, applying a composition in which a main agent component and a curing agent component are mixed to a desired location to form a coating film, and then reacting and curing the composition.

[0173] (Sealing material)

[0174] The polythioether resin used in the polythioether sealing material is not particularly limited as long as it has a thioether bond in the molecule, and examples thereof include a resin having a hydrocarbon group such as an alkyl group bonded to the thioether bond. The polythioether resin may have, for example, an ether bond, an ester bond, an amide bond, or an imide group in its skeleton.

[0175] When the polythioether resin has an ether bond in the skeleton, it is a polythioether polyether resin. The polythioether resin may have a functional group such as a thiol group, a hydroxyl group, or an amino group at one or both ends.

[0176] Examples of the polythioether resin include a polythioether resin having a structural unit represented by -(C2H4OCH2OC2H4-Sx)- (x is an integer of 1 to 5) in the main chain and a thiol group represented by -C2H4OCH2OC2H4-SH at the terminal.

[0177] The polysulfide ether resin preferably has fluidity at room temperature, specifically, at 25° C. The number average molecular weight (Mn) of the polysulfide ether resin is usually 100 to 200,000, and preferably 400 to 50,000 or less.

[0178] In addition, the polythioether resins mentioned above may also include polythioether polyether resins. Specifically, the polythioether polyether resins include polythioether polyether resins containing thiol groups, for example, polythioether polyether resins containing (1) "-(R1O)" in the main chain. n (R1 represents an alkylene group having 2 to 4 carbon atoms, and n represents an integer from 6 to 200.), (2) structural units represented by "-C2H4OCH2OC2H4-Sx-" and (3) "-CH2CH(OH)CH2-Sx-" (the above x is an integer from 1 to 5.), and a polythioether polyether resin having a thiol group represented by (4) "-C2H4OCH2OC2H4-SH" or "-CH2CH(OH)CH2-SH" at the end.

[0179] The number average molecular weight of the polysulfide polyether resin is generally 600 to 200,000, preferably 800 to 50,000.

[0180] The method for producing the polythioether resin is not limited, and polythioether resins produced by various known methods can be used. In addition, commercially available polythioether resins can also be used. Commercially available polythioether resins include, for example, "Thiocol LP-23, LP-32" (manufactured by TORAY FINE CHEMICALS Co., Ltd.), "THIOPLAST polymer" (manufactured by AKZO NOBEL Co., Ltd.), etc. The polythioether resin can be used alone or in combination of two or more.

[0181] The polysulfide-based sealing material containing the dispersion stabilizer of the present invention may be used in combination with various other additives, etc. Examples of the additives include the above-mentioned viscosity reducing agent, the above-mentioned plasticizer, an adhesive imparting agent, a pigment, a dye, an anti-aging agent, an antioxidant, an antistatic agent, a flame retardant, a tackifying resin, a stabilizer, a dispersant, etc.

[0182] Examples of the adhesion-imparting agent include silane coupling agents such as aminosilane, and are particularly preferred because they are excellent in the effect of improving adhesion to a glass surface and are general-purpose compounds.

[0183] Examples of the aminosilane include 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropylmethyldimethoxysilane, 3-aminopropylethyldiethoxysilane, bistrimethoxysilylpropylamine, bistriethoxysilylpropylamine, bismethoxydimethoxysilylpropylamine, bisethoxydiethoxysilylpropylamine, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltriethoxysilane, and N-2-(aminoethyl)-3-aminopropylethyldiethoxysilane.

[0184] Examples of the pigment include organic pigments such as azo pigments and copper phthalocyanine pigments.

[0185] Examples of the dye include a black dye, a yellow dye, a red dye, a blue dye, and a brown dye.

[0186] Examples of the antioxidant include hindered phenol compounds and hindered amine compounds.

[0187] Examples of the antioxidant include butylhydroxytoluene (BHT) and butylhydroxyanisole (BHA).

[0188] Examples of the antistatic agent include quaternary ammonium salts; and hydrophilic compounds such as polyethylene glycol and ethylene oxide derivatives.

[0189] Examples of the flame retardant include chloroalkyl phosphates, dimethyl methylphosphonate, bromine phosphorus compounds, ammonium polyphosphate, neopentyl bromide-polyether, and brominated polyether.

[0190] Examples of the tackifier resin include terpene resins, phenolic resins, terpene-phenolic resins, rosin resins, xylene resins, epoxy resins, alkyl titanates, and organic polyisocyanates.

[0191] Examples of the stabilizer include fatty acid silyl esters and fatty acid amide trimethylsilyl compounds.

[0192] The dispersant is a substance that disperses a solid in a liquid in the form of fine particles, and examples thereof include sodium hexametaphosphate, condensed sodium naphthalenesulfonate, and surfactants.

[0193] The polysulfide-based sealing material is usually mixed with a curing agent immediately before use. As the curing agent, for example, a curing agent commonly used for polysulfide resin-based sealing materials such as metal oxides, metal peroxides, organic and inorganic oxidants, epoxy compounds, and isocyanate compounds can be used. Among them, metal peroxides such as lead dioxide and manganese dioxide are preferred, and manganese dioxide is more preferred. The fluidity modifier of the present invention is preferably mixed with the curing agent for use.

[0194] When manganese dioxide is used as the curing agent, the amount used is preferably in the range of 2.5 to 25 parts by mass, more preferably in the range of 3 to 20 parts by mass, based on 100 parts by mass of the polysulfide resin used as the main agent, from the viewpoint of sufficient curing and obtaining a cured product having appropriate elasticity.

[0195] The curing agent may contain other fillers, plasticizers, curing accelerators, and silane coupling agents.

[0196] When used as a sealing material, the curing conditions are usually 20 to 25° C. after the main agent and the curing agent are mixed. The curing time is usually in the range of 24 to 168 hours.

[0197] The inorganic filler-containing resin composition of the present invention is not limited to the above-mentioned paste resin composition, and can also be suitably used as a molding resin composition for injection molding, extrusion molding, etc. The properties of the molding resin composition are various, and it is liquid at the stage before molding (normal temperature), or becomes liquid by heating during molding, but the dispersion stabilizer of the present invention can reduce the viscosity of the composition and inhibit the formation of hard cakes, thereby inhibiting the excessive viscosity increase caused by the inclusion of inorganic fillers, and can smoothly perform melt kneading before molding.

[0198] The dispersion stabilizer of the present invention can also increase the amount of inorganic filler added, and therefore can be suitably used in resin compositions for molding such as automotive parts, sanitary absorbent articles, building materials, stone paper, and heat dissipation parts, which are expected to increase the amount of inorganic filler added to improve physical properties.

[0199] Hereinafter, composition examples for different applications when the inorganic filler-containing resin composition of the present invention is used as a molding resin composition will be described.

[0200] (Automotive components)

[0201] The resin component contained in the molding resin composition used for automobile parts (hereinafter sometimes simply referred to as "automobile part resin composition") is, for example, a thermoplastic resin. Among the thermoplastic resins, a polypropylene resin having excellent moldability, high mechanical strength, and economic efficiency is preferred.

[0202] The polypropylene is not particularly limited, but is preferably a polypropylene resin having an MFR (230° C., 2.16 kg) of 60 to 120 g / 10 min.

[0203] The resin composition for automobile parts may further contain an olefin-based thermoplastic elastomer as a resin component. The olefin-based thermoplastic elastomer is not particularly limited, but preferably contains an ethylene-α-olefin copolymer.

[0204] Examples of the inorganic filler contained in the resin composition for automobile parts include talc, calcium carbonate, whiskers (the material of the whiskers is graphite, potassium titanate, aluminum oxide, silicon carbide, silicon nitride, mullite, magnesium oxide, magnesium borate, aluminum borate, magnesium sulfate, zinc oxide, titanium boride, etc.), carbon nanofibers, carbon nanotubes, kaolin, mica, etc.

[0205] The resin composition for automobile parts may contain various additives other than the dispersion stabilizer and inorganic filler of the present invention. Examples of such additives include the above-mentioned viscosity reducing agent, the above-mentioned plasticizer, antioxidant, ultraviolet absorber, light stabilizer, flame retardant, colorant and the like.

[0206] The composition ratio of the resin component, inorganic filler, dispersion stabilizer, etc. contained in the resin composition for automobile parts is not particularly limited, but is preferably adjusted to a composition that satisfies one or more of the following physical properties.

[0207] The MFR (230° C., 2.16 kg, JIS-K7210-1) of the resin composition for automobile parts is preferably 20 g / 10 min or more, more preferably in the range of 20 to 30 g / 10 min.

[0208] The linear expansion coefficient (JIS-K7197) of the resin composition for automobile parts is preferably 5.0×10 -5 / K or less, more preferably 4.0 to 5.0×10 -5 / K.

[0209] The tensile elastic modulus (JIS-K7161) of the resin composition for automobile parts is preferably 2.5 GPa or more, more preferably in the range of 2.5 to 3.0 GPa.

[0210] The Charpy impact value (JIS-K7111) of the resin composition for automobile parts is preferably 30 kJ / m 2 More preferably, 30 to 40 kJ / m 2range.

[0211] Examples of automobile parts obtained by molding the resin composition for automobile parts include hoods, fenders, bumpers, doors, trunk lids, roofs, radiator grilles, hub caps, instrument panels, pillar garnishes, and the like.

[0212] These automobile parts can be produced by injection molding the resin composition for automobile parts.

[0213] (hygienic absorbent articles)

[0214] The resin component contained in the molding resin composition used in sanitary absorbent articles (hereinafter sometimes referred to as "resin composition for sanitary absorbent articles") is, for example, a polyolefin, and among the polyolefins, at least one selected from polyethylene and polypropylene is preferred, and polyethylene is more preferred.

[0215] When polyethylene is used as the resin component, for example, two or more types of polyethylene having different densities may be used.

[0216] The polyolefin as the resin component of the resin composition for sanitary absorbent articles is not particularly limited, but MFR (190° C., 2.16 kgf) is preferably in the range of 0.1 to 20 g / 10 min, more preferably in the range of 0.5 to 5 g / 10 min.

[0217] By setting the MFR to 0.1 g / 10 minutes or more, the formability of the film can be sufficiently maintained, and by setting the MFR to 20 g / 10 minutes or less, sufficient strength can be obtained.

[0218] The resin composition for sanitary absorbent articles may further contain a polystyrene-based elastomer as a resin component.

[0219] Examples of the polystyrene elastomers include styrene block-containing elastomers of styrene-olefin (SEP, SEBC, etc.), styrene-olefin-styrene (SEPS, SEBS, etc.), styrene-diene (SIS, SBS, etc.), and hydrogenated styrene-diene (HSIS, HSBR, etc.).

[0220] The content of the styrene component in these polystyrene-based elastomers is preferably in the range of 10 to 40% by mass, more preferably in the range of 20 to 40% by mass.

[0221] Examples of the inorganic filler contained in the resin composition for sanitary absorbent articles include calcium carbonate, calcium sulfate, barium carbonate, titanium oxide, and the like. Preferably, the inorganic filler is at least one selected from calcium carbonate and barium sulfate.

[0222] The shape of these inorganic fillers is not particularly limited, but is preferably in the form of particles, more preferably fine particles with an average particle size in the range of 0.1 to 10 μm, further preferably fine particles with an average particle size in the range of 0.3 to 5 μm, and particularly preferably fine particles with an average particle size in the range of 0.5 to 3 μm.

[0223] The content of the inorganic filler in the resin composition for sanitary absorbent articles is, for example, preferably polyolefin:inorganic filler = 60 to 20 parts by mass:40 to 80 parts by mass, more preferably polyolefin:inorganic filler = 55 to 25 parts by mass:45 to 75 parts by mass, and still more preferably polyolefin:inorganic filler = 50 to 30 parts by mass:50 to 70 parts by mass.

[0224] When the content of the inorganic filler is within the above range, all of the moisture permeability, air permeability, and liquid permeation resistance of the obtained sanitary absorbent article can be sufficiently ensured.

[0225] The resin composition for sanitary absorbent articles may contain various additives other than the dispersion stabilizer and inorganic filler of the present invention. Examples of such additives include the above-mentioned viscosity reducing agent, the above-mentioned plasticizer, a compatibilizer, a processing aid, an antioxidant, a heat stabilizer, a light stabilizer, an ultraviolet absorber, an anti-blocking agent, an antifogging agent, a matting agent, a surfactant, an antibacterial agent, a deodorant, an antistatic agent, a water-repellent agent, an oleophobic agent, a radiation shielding agent, a colorant, a pigment, and the like.

[0226] The molded article obtained by molding the resin composition for sanitary absorbent articles can be suitably used as a back sheet (a sheet having air permeability and moisture permeability but preventing liquid from passing) used in sanitary absorbent articles such as disposable diapers and sanitary products.

[0227] The back sheet can be produced, for example, by melt-kneading the resin composition for sanitary absorbent articles, forming a sheet by a T-die method or an inflation method, and then uniaxially or biaxially stretching the obtained sheet.

[0228] (Stone Paper)

[0229] Stone paper is a sheet made of calcium carbonate from limestone and polyolefins (polyethylene, polypropylene, etc.). The sheet does not require water or wood to be formed, and the limestone used as the raw material is almost infinite on the earth, so it is a sheet with excellent sustainability.

[0230] Stone paper contains a large amount of calcium carbonate, but the dispersion stabilizer of the present invention can improve the fluidity of calcium carbonate, thereby improving the physical properties of the sheet.

[0231] Stone paper can be produced, for example, by melt-kneading a stone paper composition containing calcium carbonate, polyolefin and the dispersion stabilizer of the present invention, and then performing inflation molding or extrusion molding.

[0232] In the stone paper composition, the content of calcium carbonate is, for example, 85:15 to 20:80, preferably 85:15 to 30:70, more preferably 85:15 to 35:65, and further preferably 80:20 to 40:60, in terms of the mass ratio of polyolefin to calcium carbonate (polyolefin:calcium carbonate).

[0233] The stone paper composition may further contain the above-mentioned viscosity reducing agent, the above-mentioned plasticizer, a foaming agent, a colorant, a lubricant, a coupling agent, a stabilizer (antioxidant, ultraviolet absorber, etc.), an antistatic agent, etc. as auxiliary agents.

[0234] Examples of the foaming agent include aliphatic hydrocarbon compounds such as propane, n-butane, isobutane, n-pentane, isopentane, and hexane; alicyclic hydrocarbon compounds such as cyclohexane, cyclopentane, and cyclobutane; and halogenated hydrocarbon compounds such as trifluoromonochloroethane and difluorodichloromethane.

[0235] Examples of the lubricant include fatty acid lubricants such as stearic acid, hydroxystearic acid, complex stearic acid, and oleic acid; aliphatic amide lubricants such as aliphatic alcohol lubricants, stearamide, oxystearamide, oleamide, erucamide, ricinolamide, behenamide, hydroxymethylamide, methylenebisstearamide, methylenebisstearylbehenamide, bisamide acids of higher fatty acids, and complex amides; aliphatic ester lubricants such as n-butyl stearate, methyl hydroxystearate, polyol fatty acid esters, saturated fatty acid esters, and ester waxes; fatty acid metal soap lubricants, and the like.

[0236] As the antioxidant, a phosphorus antioxidant, a phenol antioxidant, a pentaerythritol antioxidant, or the like can be used.

[0237] As the phosphorus-based antioxidant, there can be mentioned phosphites such as triesters, diesters, and monoesters of phosphorous acid such as triphenyl phosphite, tris(nonylphenyl) phosphite, and tris(2,4-di-tert-butylphenyl) phosphite; and phosphates such as trimethyl phosphate, triethyl phosphate, tributyl phosphate, trioctyl phosphate, triphenyl phosphate, tricresyl phosphate, tris(nonylphenyl) phosphate, and 2-ethylphenyldiphenyl phosphate.

[0238] Examples of the phenolic antioxidant include α-tocopherol, butylhydroxytoluene, sinapyl alcohol, vitamin E, n-octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 2-tert-butyl-6-(3'-tert-butyl-5'-methyl-2'-hydroxybenzyl)-4-methylphenylacrylate, 2,6-di-tert-butyl-4-(N,N-dimethylaminomethyl)phenol, diethyl 3,5-di-tert-butyl-4-hydroxybenzylphosphonate, and tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyloxymethyl]methane.

[0239] (Heat dissipation component)

[0240] In electronic devices such as personal computers, smartphones, and televisions, the amount of heat generated increases with the performance improvement. In order to efficiently dissipate the generated heat, heat dissipation components containing thermally conductive fillers are often used. In addition, automobiles such as electric vehicles and hybrid vehicles also have many electronic devices, and most of them use heat dissipation components containing thermally conductive fillers.

[0241] Examples of the resin component contained in the molding resin composition used for the heat dissipation member (hereinafter, sometimes simply referred to as "resin composition for heat dissipation member") include thermosetting resins, active energy ray-curable resins, and thermoplastic resins.

[0242] As the thermosetting resin of the resin composition for heat dissipation components, known thermosetting resins can be used, for example, phenolic phenolic resins such as phenol novolac resin and cresol novolac resin; phenolic resins such as unmodified resol phenolic resin and oil-modified resol phenolic resin modified with tung oil, linseed oil, walnut oil, etc.; bisphenol-type epoxy resins such as bisphenol A epoxy resin and bisphenol F epoxy resin; phenolic epoxy resins such as fatty chain-modified bisphenol-type epoxy resin, novolac epoxy resin, and cresol novolac epoxy resin; epoxy resins such as biphenyl epoxy resin and polyalkylene glycol epoxy resin; resins having a triazine ring such as urea resin and melamine resin; vinyl resins such as (meth) acrylic resin and vinyl ester resin; unsaturated polyester resin, bismaleimide resin, polyurethane resin, diallyl phthalate resin, silicone resin, resin having a benzoxazine ring, cyanate ester resin, etc.

[0243] The above-mentioned thermosetting resin may be used together with a curing agent.

[0244] Examples of the curing agent used together with the thermosetting resin include amine compounds such as diaminodiphenylmethane, diethylenetriamine, triethylenetetramine, diaminodiphenylsulfone, isophoronediamine, imidazole, BF3-amine complex, and guanidine derivatives; amide compounds such as dicyandiamide and polyamide resin synthesized from a dimer of linolenic acid and ethylenediamine; phthalic anhydride, trimellitic anhydride, pyromellitic anhydride, maleic anhydride, tetrahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylnadic anhydride, hexahydrophthalic anhydride, methylhexahydrophthalic anhydride and other anhydride compounds; phenol novolac resin, cresol novolac resin, aromatic hydrocarbon formaldehyde resin modified phenolic resin, dicyclopentadiene phenol addition type resin, phenol aralkyl resin (Xylok resin), resorcinol novolac resin, naphthol aralkyl resin, trimethylolmethane resin, tetrahydroxyphenylethane resin, naphthol novolac resin, naphthol-phenol co-condensation phenolic resin, naphthol-cresol co-condensation phenolic resin, biphenyl modified phenolic resin, biphenyl modified naphthol resin, aminotriazine modified phenolic resin, alkoxy-containing aromatic ring modified phenolic resin and other phenolic compounds.

[0245] As the thermoplastic resin of the resin composition for heat dissipation components, known thermoplastic resins can be used, for example, polyethylene resin, polypropylene resin, polymethyl methacrylate resin, polyvinyl acetate resin, ethylene-propylene copolymer, ethylene-vinyl acetate copolymer, polyvinyl chloride resin, polystyrene resin, polyacrylonitrile resin, polyamide resin, polycarbonate resin, polyacetal resin, polyethylene terephthalate resin, polyphenylene ether resin, polyphenylene sulfide resin, polysulfone resin, polyethersulfone resin, polyetheretherketone resin, polyallyl sulfone resin, thermoplastic polyimide resin, thermoplastic urethane resin, polyaminobismaleimide resin, polyamideimide resin, polyetherimide resin, bismaleimide triazine resin, polymethylpentene resin, fluorinated resin, liquid crystal polymer, olefin-vinyl alcohol copolymer, ionomer resin, polyarylate resin, acrylonitrile-ethylene-styrene copolymer, acrylonitrile-butadiene-styrene copolymer, acrylonitrile-styrene copolymer, etc.

[0246] Examples of the thermally conductive filler contained in the resin composition for a heat dissipating member include aluminum oxide, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, calcium silicate, calcium oxide, magnesium oxide, zinc oxide, beryllium oxide, aluminum oxide, aluminum nitride, boron nitride, hydrated metal compounds, fused silica, crystalline silica, amorphous silica, silicon carbide, silicon nitride, titanium carbide, and diamond.

[0247] The thermally conductive filler may be a filler surface-treated with a silane-based, titanate-based, or aluminate-based coupling agent or the like.

[0248] The shape of the thermally conductive filler is not particularly limited, and may be any of spherical, needle-like, flake-like, dendritic, and fibrous.

[0249] The content of the thermally conductive filler in the resin composition for heat dissipating members can be appropriately adjusted depending on the intended use, but is preferably within a range of 30 to 500 parts by mass based on 100 parts by mass of the resin component.

[0250] The resin composition for heat dissipation components may contain various additives other than the inorganic filler dispersion stabilizer and thermally conductive filler of the present invention. Examples of such additives include dyes, pigments, antioxidants, inhibitors, defoaming agents, leveling agents, ion traps, moisturizers, viscosity modifiers, preservatives, antibacterial agents, antistatic agents, antiblocking agents, ultraviolet absorbers, infrared absorbers, and the like.

[0251] When the resin composition for heat dissipation components contains a thermosetting resin, the heat dissipation components can be formed by heating the resin composition for heat dissipation components. When the resin composition for heat dissipation components contains an active energy ray-curable resin, the heat dissipation components can be cured and formed by irradiating active energy rays such as ultraviolet rays and infrared rays. When the resin composition for heat dissipation components contains a thermoplastic resin, the heat dissipation components can be obtained by known molding methods such as injection molding, extrusion molding, and stamping molding.

[0252] The heat dissipation member obtained by molding the resin composition for heat dissipation members can be used as a heat dissipation sheet. The heat dissipation member obtained by molding the resin composition for heat dissipation members can also be used as a heat dissipation joining member for joining a portion to be radiated with a metal heat dissipation member.

[0253] The resin composition for heat dissipating members can also be used as a semiconductor sealing material.

[0254] In the above, the inorganic filler-containing resin composition has been described. However, the inorganic filler dispersion stabilizer of the present invention can improve the storage stability even in an inorganic filler-containing composition that does not contain a resin.

[0255] For example, by adding the dispersion stabilizer of the present invention to a composition containing an organic solvent such as acetone and an inorganic filler, the sedimentation rate of the inorganic filler can be reduced, thereby suppressing the formation of aggregates (hard cakes) containing the inorganic filler.

[0256] [Example]

[0257] Hereinafter, the present invention will be specifically described by way of Examples and Comparative Examples.

[0258] It should be noted that the present invention is not limited to the following examples.

[0259] In the examples of the present application, the values ​​of the acid value and the hydroxyl value are values ​​evaluated by the following method.

[0260] [Measurement method of acid value]

[0261] The measurement was conducted by a method in accordance with JIS K0070-1992.

[0262] [Method for measuring hydroxyl value]

[0263] The measurement was conducted by a method in accordance with JIS K0070-1992.

[0264] In the examples of the present application, the number average molecular weight of the polyester is a value obtained by polystyrene conversion based on GPC measurement, and the measurement conditions are as follows.

[0265] [GPC measurement conditions]

[0266] Measuring device: High-speed GPC device "HLC-8320GPC" manufactured by Tosoh Corporation

[0267] Column: "TSK GURDCOLUMN SuperHZ-L" made by Tosoh Co., Ltd. + "TSK gelSuperHZM-M" made by Tosoh Co., Ltd. + "TSK gel SuperHZM-M" made by Tosoh Co., Ltd. + "TSK gelSuperHZ-2000" made by Tosoh Co., Ltd. + "TSK gel SuperHZ-2000" made by Tosoh Co., Ltd.

[0268] Detector: RI (differential refractometer)

[0269] Data processing: Tosoh Corporation "EcoSEC Data Analysis Version 1.07"

[0270] Column temperature: 40°C

[0271] Eluent: Tetrahydrofuran

[0272] Flow rate: 0.35mL / min

[0273] Measurement sample: 7.5 mg of a sample was dissolved in 10 ml of tetrahydrofuran, and the resulting solution was filtered through a microfilter to use as a measurement sample.

[0274] Sample injection volume: 20μl

[0275] Standard sample: According to the measurement manual of the above-mentioned "HLC-8320GPC", the following monodisperse polystyrene having a known molecular weight was used.

[0276] (monodisperse polystyrene)

[0277] "A-300" manufactured by Tosoh Corporation

[0278] "A-500" manufactured by Tosoh Corporation

[0279] "A-1000" manufactured by Tosoh Corporation

[0280] "A-2500" manufactured by Tosoh Corporation

[0281] "A-5000" manufactured by Tosoh Corporation

[0282] "F-1" manufactured by Tosoh Corporation

[0283] "F-2" manufactured by Tosoh Corporation

[0284] "F-4" manufactured by Tosoh Corporation

[0285] "F-10" manufactured by Tosoh Corporation

[0286] "F-20" manufactured by Tosoh Corporation

[0287] "F-40" manufactured by Tosoh Corporation

[0288] "F-80" manufactured by Tosoh Corporation

[0289] "F-128" manufactured by Tosoh Corporation

[0290] "F-288" manufactured by Tosoh Corporation

[0291] (Example 1: Synthesis of Dispersion Stabilizer A)

[0292] In a 3-liter four-necked flask equipped with a thermometer, a stirrer, and a reflux condenser, 531.8 g of 3-methyl-1,5-pentanediol, 1235.1 g of sebacic acid, and 0.0053 g of tetraisopropyl titanate as an esterification catalyst were placed, and the temperature was gradually raised to 220° C. under a nitrogen stream while stirring, thereby performing a condensation reaction for a total of 10 hours. After the reaction was completed, unreacted components were removed by distillation under reduced pressure, thereby obtaining a dispersion stabilizer A (acid value 110, hydroxyl value 0, number average molecular weight 1000) containing a polyester having carboxyl groups at both ends.

[0293] (Example 2: Synthesis of Dispersion Stabilizer B)

[0294] In a 3-liter four-necked flask equipped with a thermometer, a stirrer, and a reflux condenser, 625.5 g of 3-methyl-1,5-pentanediol, 1702.5 g of 1,12-dodecanedioic acid, and 0.069 g of tetraisopropyl titanate as an esterification catalyst were added, and the temperature was gradually raised to 220° C. under a nitrogen stream while stirring, thereby performing a condensation reaction for a total of 10 hours. After the reaction was completed, unreacted components were removed by distillation under reduced pressure, thereby obtaining a dispersion stabilizer B (acid value 108.5, hydroxyl value 0.01, number average molecular weight 1000) containing a polyester having carboxyl groups at both ends.

[0295] (Example 3: Synthesis of Dispersion Stabilizer C)

[0296] In a 2-liter four-necked flask equipped with a thermometer, a stirrer, and a reflux condenser, 1214 g of 3-methyl-1,5-pentanediol, 966 g of sebacic acid, and 0.07 g of tetraisopropyl titanate as an esterification catalyst were placed, and the temperature was gradually raised to 220° C. under a nitrogen stream while stirring, thereby performing a condensation reaction for a total of 12 hours. After the reaction, 0.11 g of hydroquinone and 203 g of maleic anhydride were added at 150° C. to terminate the reaction, thereby obtaining a dispersion stabilizer C (acid value 24.7, hydroxyl value 64, number average molecular weight 1700) containing a polyester having carboxyl groups at both ends.

[0297] The dispersion stabilizer C was confirmed to contain a polyester having carboxyl groups at both ends by MALDI-TOF / MS measurement. Specifically, the dispersion stabilizer C was analyzed using a matrix-assisted laser desorption ionization time-of-flight mass spectrometer (AXIMATOF2 manufactured by Shimadzu Corporation), and a molecular weight of 621 (M+Na) observed when carboxyl groups were present at both ends was detected in the polyester using sebacic acid, 3-methyl-1,5-pentanediol and maleic acid as reaction raw materials. + and 905(M+Na) + .

[0298] The measurement results are shown in Figure 1 .

[0299] (Example 4: Synthesis of Dispersion Stabilizer D)

[0300] In a 2-liter four-necked flask equipped with a thermometer, a stirrer, and a reflux condenser, 395.7 g of propylene glycol, 809.0 g of sebacic acid, and 0.07 g of tetraisopropyl titanate as an esterification catalyst were added, and the temperature was gradually raised to 220° C. under a nitrogen stream while stirring, thereby performing a condensation reaction for a total of 12 hours. After the reaction, 0.06 g of hydroquinone and 109.8 g of maleic anhydride were added at 150° C. to terminate the reaction, thereby obtaining a dispersion stabilizer D (acid value 44.8, hydroxyl value 38.0, number average molecular weight 1840) containing a polyester having carboxyl groups at both ends.

[0301] (Example 5: Synthesis of Dispersion Stabilizer E)

[0302] In a 2-liter four-necked flask equipped with a thermometer, a stirrer, and a reflux condenser, 1214 g of 3-methyl-1,5-pentanediol, 966 g of sebacic acid, and 0.07 g of tetraisopropyl titanate as an esterification catalyst were added, and the temperature was gradually raised to 220° C. under a nitrogen stream while stirring, thereby performing a condensation reaction for a total of 12 hours. After the reaction, 306.7 g of phthalic anhydride was added at 150° C. to terminate the reaction, and a dispersion stabilizer E (acid value 49.0, hydroxyl value 48.4, number average molecular weight 1170) containing a polyester having carboxyl groups at both ends was obtained.

[0303] (Example 6: Synthesis of Dispersion Stabilizer F)

[0304] In a 2-liter four-necked flask equipped with a thermometer, a stirrer, and a reflux condenser, 459.3 g of 1,3-butanediol, 48.7 g of neopentyl glycol, 616.2 g of adipic acid, and 0.112 g of tetraisopropyl titanate as an esterification catalyst were added, and the temperature was gradually raised to 220° C. under a nitrogen stream while stirring, thereby performing a condensation reaction for a total of 10 hours. After the reaction, 0.056 g of hydroquinone and 44.2 g of maleic anhydride were added at 150° C. to terminate the reaction, thereby obtaining a dispersion stabilizer F (acid value 29.1, hydroxyl value 121, number average molecular weight 900) containing a polyester having carboxyl groups at both ends.

[0305] (Synthesis Example 1: Synthesis of Viscosity Reducing Agent A)

[0306] In a 3-liter four-necked flask equipped with a thermometer, a stirrer, and a reflux condenser, 1680 g of 12-hydroxystearic acid and 0.252 g of tetraisopropyl titanate as an esterification catalyst were placed, and the temperature was gradually raised to 210° C. under a nitrogen stream while stirring, thereby performing a condensation reaction for a total of 15 hours. After the reaction was completed, unreacted components were removed by distillation under reduced pressure, thereby obtaining a viscosity reducing agent A (acid value 29.7, hydroxyl value 19.1, number average molecular weight 1800) which is a polyester having a carboxyl group at one end and a hydroxyl group at the other end.

[0307] (Examples 7-15 and Comparative Examples 1-5: Preparation and Evaluation of Compositions Containing Calcium Carbonate)

[0308] Calcium carbonate (heavy calcium carbonate, "Super S" manufactured by Maruo Calcium Co., Ltd.) as an inorganic filler, DINP (diisononyl phthalate) as a plasticizer, DETDA (diethyltoluenediamine) as an active hydrogen compound, a dispersion stabilizer and a viscosity reducer were mixed in the proportions shown in Tables 1 and 2, and stirred at 1000 rpm and 0.2 Pa for 2 minutes using a planetary stirring device (THINKY ARV-310) to obtain a paste-like inorganic filler-containing composition.

[0309] The viscosity and storage stability of the obtained paste composition were evaluated by the following methods.

[0310] [Viscosity measurement method]

[0311] The viscosity of the obtained paste was measured using an E-type viscometer (TV-25H manufactured by Toyo Sangyo Co., Ltd.) using a standard rotor (1°34'×R24, shear rate [1 / S] 3.83×N, N is the rotation speed [rpm] of the rotor). Specifically, the obtained paste was treated at a measurement temperature of 25°C and a rotation speed of 10 rpm, and the viscosity value of the composition after 3 minutes of treatment was read.

[0312] [Evaluation of storage stability]

[0313] 12 g of the obtained composition was stored in a 50 cc glass bottle and left in a thermostat at 50° C. for 2 weeks.

[0314] The composition after standing was confirmed by visual inspection and touch, and evaluated according to the following criteria.

[0315] ○: The presence of inorganic filler aggregates (hard cakes) could not be confirmed

[0316] ×: The presence of agglomerates (hard cakes) of inorganic fillers can be confirmed

[0317]

Table 1

[0318]

[0319]

Table 2

[0320]

[0321] The evaluation results of Examples 7-10 and Comparative Examples 4-5 show that in the paste using both the inorganic filler dispersant stabilizer and the viscosity reducing agent of the present invention, although the viscosity slightly increases, the storage stability is significantly improved. In addition, the evaluation results of Examples 11-15 and Comparative Examples 1-3 show that the inorganic filler dispersant stabilizer of the present invention can fully exhibit not only the storage stabilization effect, but also the viscosity reducing effect.

[0322] (Examples 16-18 and Comparative Examples 6-8: Preparation and Evaluation of Resin Compositions Containing Calcium Carbonate)

[0323] Calcium carbonate (heavy calcium carbonate, "Super S" manufactured by Maruo Calcium Co., Ltd.) as an inorganic filler, polyethylene ("UMERIT 2040F" manufactured by Ube Industries, Ltd.) as a binder resin, a dispersion stabilizer and a viscosity reducer were mixed in the proportions shown in Table 3, put into a batch mixer ("Labo Plastomill 4C150" manufactured by Toyo Seiki Seisaku-sho, Ltd.), and melt-kneaded at a set temperature of 170°C, a blade speed of 50 r / min, and a kneading time of 10 minutes to prepare a resin composition containing an inorganic filler.

[0324] The torque value and internal temperature during melt kneading when preparing the inorganic filler-containing resin composition were evaluated. The results are shown in Table 3. The torque value and internal temperature were obtained by reading the display values ​​of the kneading machine when the kneading time was 8 minutes.

[0325]

Table 3

[0326]

[0327] The evaluation results of Examples 16 to 18 and Comparative Examples 6 to 8 show that the resin composition containing the inorganic filler dispersion stabilizer of the present invention has a reduced torque value and suppressed temperature rise, and the resin composition is reduced in viscosity by the inorganic filler dispersion stabilizer of the present invention.

[0328] (Example 19 and Comparative Examples 9-10: Preparation and Evaluation of Talc-Containing Resin Compositions)

[0329] 10.8 g of talc ("RL217" manufactured by Fuji Talc Industry Co., Ltd.) as an inorganic filler, 36 g of polypropylene (homopolymer of polypropylene, "J106G" manufactured by Prime Polymer Co., Ltd.) as a binder resin, a dispersion stabilizer and a viscosity reducer were mixed in the proportions shown in Table 4, put into a batch mixer ("Labo Plastomill4C150" manufactured by Toyo Seiki Seisaku-sho, Ltd.), and melt-kneaded at a set temperature of 170°C, a blade speed of 50 r / min, and a kneading time of 10 minutes to prepare a resin composition.

[0330] The torque value and internal temperature during melt kneading were evaluated.

[0331] The torque value and the internal temperature were obtained by reading the display values ​​of the kneading machine after kneading for 8 minutes.

[0332]

Table 4

[0333]

[0334] The evaluation results of Example 19 and Comparative Examples 9-10 show that the resin composition containing the inorganic filler dispersion stabilizer of the present invention has a reduced torque value and a suppressed temperature rise, and that the resin composition is reduced in viscosity by the inorganic filler dispersion stabilizer of the present invention.

[0335] (Example 20: Synthesis of Dispersion Stabilizer G)

[0336] In a 5-liter four-necked flask equipped with a thermometer, a stirrer, and a reflux condenser, 1,3-butanediol 1634 g, neopentyl glycol 210 g, adipic acid 2338 g, and tetraisopropyl titanate 0.125 g as an esterification catalyst were placed, and the temperature was gradually raised to 220° C. under a nitrogen stream while stirring, thereby performing a condensation reaction for a total of 16 hours. After the reaction, maleic anhydride 373 g was added at 125° C. to terminate the reaction, and a dispersion stabilizer G (acid value 55, hydroxyl value 53, number average molecular weight 1190) containing a polyester having carboxyl groups at both ends was obtained.

[0337] (Example 21: Synthesis of Dispersion Stabilizer H)

[0338] In a 5-liter four-necked flask equipped with a thermometer, a stirrer, and a reflux condenser, 1,3-butanediol 1394 g, neopentyl glycol 179 g, sebacic acid 2629 g, and tetraisopropyl titanate 0.126 g as an esterification catalyst were added, and the temperature was gradually raised to 220° C. under a nitrogen stream while stirring, thereby performing a condensation reaction for a total of 17 hours. After the reaction, maleic anhydride 387 g was added at 125° C. to terminate the reaction, and a dispersion stabilizer H (acid value 56, hydroxyl value 43, number average molecular weight 1550) containing a polyester having carboxyl groups at both ends was obtained.

[0339] (Example 22: Synthesis of Dispersion Stabilizer I)

[0340] In a 3-liter four-necked flask equipped with a thermometer, a stirrer, and a reflux condenser, 1214 g of 3-methyl-1,5-pentanediol, 966 g of sebacic acid, and 0.07 g of tetraisopropyl titanate as an esterification catalyst were added, and the temperature was gradually raised to 220° C. under a nitrogen stream while stirring, thereby performing a condensation reaction for a total of 12 hours. After the reaction, 271 g of maleic anhydride was added at 125° C. to terminate the reaction, and a dispersion stabilizer I (acid value 65, hydroxyl value 35, number average molecular weight 1540) containing a polyester having carboxyl groups at both ends was obtained.

[0341] (Example 23: Synthesis of Dispersion Stabilizer J)

[0342] Into a 3 liter four-necked flask equipped with a thermometer, a stirrer and a reflux condenser were placed 473 g of 3-methyl-1,5-pentanediol, 850 g of sebacic acid and 0.04 g of tetraisopropyl titanate as an esterification catalyst. The temperature was gradually raised to 220° C. under a nitrogen stream while stirring. The condensation reaction was carried out for a total of 13 hours to obtain a dispersion stabilizer J (acid value 22, hydroxyl value 1, number average molecular weight 4320) containing a polyester having carboxyl groups at both ends.

[0343] (Examples 24-27: Preparation and evaluation of compositions containing calcium carbonate)

[0344] Calcium carbonate (heavy calcium carbonate, "Super S" manufactured by Maruo Calcium Co., Ltd.) as an inorganic filler, DINP (diisononyl phthalate) as a plasticizer, DETDA (diethyltoluenediamine) as an active hydrogen compound, a dispersion stabilizer and a viscosity reducing agent were mixed in the proportions shown in Table 5, and stirred at 1000 rpm and 0.2 Pa for 2 minutes using a planetary stirring device (THINKY ARV-310) to obtain a paste-like inorganic filler-containing composition.

[0345] The viscosity and storage stability of the obtained paste were evaluated in the same manner as above. The results are shown in Table 5.

[0346]

Table 5

[0347]

[0348] (Examples 28-30 and Comparative Examples 11-16: Preparation and Evaluation of Alumina-Containing Compositions)

[0349] Alumina (high-purity alumina, "AKP-3000" manufactured by Sumitomo Chemical Co., Ltd.) as an inorganic filler, a cycloaliphatic epoxy resin ("Celloxide 2021P" manufactured by Daicel Co., Ltd.) or a bisphenol A epoxy resin ("EPICLON 850-S" manufactured by DIC Corporation) as a binder resin, a dispersion stabilizer and a viscosity reducer are mixed in the proportions shown in Table 6, and stirred at 1000 rpm and 0.2 Pa for 2 minutes using a planetary stirring device (THINKY ARV-310) to obtain a composition containing an inorganic filler.

[0350] The fluidity and complex viscosity of the obtained composition were evaluated by the methods shown below, and the storage stability was evaluated by the same method as above. The results are shown in Tables 6 and 7.

[0351] [Complex viscosity]

[0352] The obtained composition was subjected to frequency dependence measurement by dynamic viscoelasticity measurement using MCR-302 (manufactured by Anton Paar Co., Ltd.) Specifically, parallel plates (diameter: 20 mm) were used, the measurement temperature was set to 25° C., the shear strain was set to 0.01%, the angular frequency was set to the range of 0.1 to 100 rad / s, and the complex viscosity at the angular frequency of 1 rad / s was obtained.

[0353] [Evaluation of liquidity]

[0354] About 0.2 g of the obtained composition was dripped onto a horizontal glass substrate using a dropper. After the dripping, the glass substrate was tilted at an angle of 80° relative to the horizontal, and the situation where the composition on the glass substrate flowed from the glass substrate was evaluated as "○", and the situation where the composition did not flow from the glass substrate but stayed was evaluated as "×". The evaluation was performed at 25°C.

[0355]

Table 6

[0356]

[0357]

Table 7

[0358]

[0359] The results of Tables 6 and 7 show that the viscosity reducing agent A cannot exhibit a viscosity reducing effect in the composition containing the epoxy resin.

[0360] (Examples 31-32 and Comparative Examples 17-19: Preparation and Evaluation of Alumina-Containing Compositions)

[0361] Alumina (high-purity alumina, "AKP-3000" manufactured by Sumitomo Chemical Co., Ltd.) as an inorganic filler, acetone, a dispersion stabilizer and a viscosity reducing agent were mixed in the proportions shown in Table 8, and stirred at 1000 rpm and 0.2 Pa for 2 minutes using a planetary stirring device (THINKY ARV-310) to obtain a composition containing an inorganic filler.

[0362] The fluidity and storage stability of the obtained composition were evaluated by the methods shown below. The results are shown in Table 8.

[0363] [Evaluation of liquidity]

[0364] About 0.2 g of the obtained composition was dripped onto a horizontal glass substrate using a dropper. After the dripping, the glass substrate was tilted at an angle of 80° relative to the horizontal, and the situation where the composition on the glass substrate flowed from the glass substrate was evaluated as "○", and the situation where the composition did not flow from the glass substrate but stayed was evaluated as "×". The evaluation was performed at 25°C.

[0365] [Evaluation of storage stability]

[0366] 12 g of the obtained composition was stored in a 50 cc glass bottle and left in a thermostat at 25°C for 2 weeks.

[0367] The composition after standing was confirmed by visual inspection and touch, and evaluated according to the following criteria.

[0368] ○: The presence of inorganic filler aggregates (hard cakes) was not confirmed

[0369] ×: The presence of agglomerates (hard cakes) of inorganic fillers was confirmed

[0370]

Table 8

[0371]

Claims

1. An inorganic filler dispersion stabilizer, which is a polyester represented by the following general formula (1), In the general formula (1), A1 is an aliphatic dibasic acid residue having 2 to 12 carbon atoms, A2 and A3 are each independently an aliphatic polybasic acid residue having 2 to 12 carbon atoms or an aromatic polybasic acid residue having 6 to 15 carbon atoms, G1 and G2 are each independently an aliphatic diol residue having 2 to 9 carbon atoms, m represents the number of repetitions, which is an integer ranging from 1 to 20. p is an integer obtained by subtracting 1 from the number of acid functional groups of the aliphatic polybasic acid or aromatic polybasic acid of A2, q is an integer obtained by subtracting 1 from the number of acid functional groups of the aliphatic polybasic acid or aromatic polybasic acid of A3, In each repeating unit enclosed in brackets, A1 and G1 are optionally the same or different. 2 . The inorganic filler dispersion stabilizer according to claim 1 , wherein the acid value thereof is in the range of 20 mgKOH / g to 400 mgKOH / g.

3. The inorganic filler dispersion stabilizer according to claim 1 or 2, wherein the number average molecular weight is in the range of 300 to 5000. 4 . An inorganic filler-containing resin composition comprising a resin, an inorganic filler, and the inorganic filler dispersion stabilizer according to claim 1 .

5. The inorganic filler-containing resin composition according to claim 4, wherein The inorganic filler is one or more selected from the group consisting of calcium carbonate, silicon dioxide, aluminum oxide, aluminum hydroxide, talc, barium titanate, boron nitride and aluminum nitride. The inorganic filler-containing resin composition according to claim 4 or 5, further comprising a viscosity reducing agent.

7. The inorganic filler-containing resin composition according to claim 6, wherein The viscosity reducing agent is one or more selected from the group consisting of polycarboxylic acid alkylammonium salts, higher fatty acid amides, polyester acid unsaturated polyaminoamide salts, and polyesters having a carboxyl group only at one terminal. 8 . The inorganic filler-containing resin composition according to claim 4 , further comprising a plasticizer.

9. The inorganic filler-containing resin composition according to claim 4 or 5, wherein The resin is one or more selected from the group consisting of polyolefin, polyester, polysulfide, polyvinyl chloride, modified polysulfide, silicone resin, modified silicone resin, acrylic urethane resin, epoxy resin, polyurethane and acrylic resin.

10. The inorganic filler-containing resin composition according to claim 9, wherein The polyester is an unsaturated polyester. 11 . A molded article, which is a molded article of the inorganic filler-containing resin composition according to claim 4 . 12 . A waterproof material comprising polyurethane, calcium carbonate, a viscosity reducing agent and the inorganic filler dispersion stabilizer according to claim 1 . 13 . An additive comprising a plasticizer and the inorganic filler dispersion stabilizer according to claim 1 .

14. A method for storage stabilization of a composition containing an inorganic filler, wherein: The inorganic filler dispersion stabilizer according to any one of claims 1 to 3 is added to a composition containing an inorganic filler.